Chromatographic methods for the simultaneous determination of binary mixture of Saxagliptin HCl and Metformin HCl - Hanan A. Merey; Nesrin K. Ramadan; Sherine S. Diab; Azza A. Moustafa (Faculty of Pharmacy, Cairo University, 2017)
Two chromatographic methods were suggested for the simultaneous determination of a binary mixture containing Saxagliptin HCl (SAG) and Metformin HCl (MET). First method was RP-HPLC method. Chromatographic separation was done on Kinetexâ¢ columnâC18 (4.6Â ÃÂ 150Â mm, 2.6Â Âµm) using mobile phase consisted of acetonitrile:phosphate buffer pHÂ =Â 4.5Â Â±Â 0.1 adjusted with orthophosphoric acid (13:87, v/v). Isocratic elution at a flow rate 1.5Â mL/min and UV detection at 220.0Â nm was performed. Second method was spectro-densitometric method. Chromatographic separation was done on precoated silica gel aluminium plates 60 F254 as a stationary phase and developing system consisting of chloroform:methanol:formic acid (80:20:0.3, by volume). The density of the separated bands was measured by UV detector at 210.0Â nm. The proposed methods were validated as per the ICH guidelines parameters like Linearity, precision, accuracy, selectivity, limit of detection and limit of quantitation. Statistical comparison was done between the obtained results and those obtained by the reported methods, showing no significant difference with respect to accuracy and precision. Keywords: Saxagliptin HCl, Metformin HCl, RP-HPLC, TLC